KAJIAN ENERGI SURYA UNTUK PEMBANGKIT TENAGA LISTRIK - Santhiarsa, I Gusti Ngurah Nitya; Kusuma, I Gusti Bagus Wijaya (Majalah Ilmiah Teknologi Elektro, 2005)
Solar cell is an energy conversion that changed solar energy into electrical energy. The energy produced by solar cell is the most energy which safe to the environment, but the area covered of its installation will be very wide. Beside that, solar cell most depends on the intensity of sun radiation, for where its continuity is questionable and become another problem. In order to make solar energy as an electrical power generator, the weakness of the problem should be eliminated. This paper will explain how solar energy could be used as an alternative energy in order to anticipate the electrical crisis in Bali.